Bridging the gap across scales: Coupling CFD and MD/GCMC in polyurethane foam simulation. (16th March 2018) - Karimi, Mohsen; Marchisio, Daniele; Laurini, Erik; Fermeglia, Maurizio; Pricl, Sabrina
Highlights: A multi-scale framework for simulating polyurethane foam is presented. An atomistic model (MD/GCM) is coupled with a continuum model (CFD). The multi-scale modeling strategy is validated for two polyurethane systems. Efficient linking is assured by agreement level between predictions and experiments. Abstract: This work presents a multi-scale approach to reacting and expanding polyurethane (PU) foams modeling and simulation. The modeling strategy relies on two pillars: an atomistic model (molecular dynamics (MD)/Grand Canonical Monte Carlo (GCMC)) that provides liquid mixture density and reactant solubility and a continuum model (CFD) in which the expansion characteristics of the foam is modeled exploiting the results of the atomistic simulations. The resulting coupled model is validated for two different PU systems applied in four batches with chemical and physical blowing agents. The results demonstrate the efficacy and reliability of the developed model in the simulation of different PU foam properties such as apparent density and temperature evolutions.